DETERMINAN LIKUIDITAS PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI INDONESIA - Ayu Rahmawati; Nurjanah, Nurjanah; Amiruddin Yahya (IAIN Langsa, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Operating Expenses on Operating Income (BOPO), Non-Performing Financing (NPF), and Return On Assets (ROA) on the Liquidity of Islamic People's Financing Banks (BPRS) in Indonesia. This study uses a quantitative approach to secondary data in the form of time series data. The population of this research is all BPRS registered with the Financial Services Authority. The data analysis technique used in this study is multiple linear regression. The results obtained show that partially the Capital Adequacy Ratio (CAR) has a positive and insignificant effect on liquidity with a significance value of 0,941. > 0,05. Operating Expenses Operating Income (BOPO) has a negative and insignificant effect on liquidity with a significance value of 0,493 > 0,05. Non-Performing Financing (NPF) has a positive and significant effect on liquidity with a significance value of 0,005 < 0,05. And Return On Assets (ROA) has a positive and significant effect on liquidity with a significance value of 0,015 < 0,05. Simultaneously the independent variable has a significant effect on the dependent variable with a significance value of 0,001 < 0,05. This means that the Capital Adequacy Ratio (CAR), Operating Income Operating Expenses (BOPO), Non-Performing Financing (NPF), and Return On Assets (ROA) simultaneously (together) have a significant effect on liquidity at Islamic People's Financing Banks (BPRS) in Indonesia.